(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In the research, we are interested in how leading, in correlation with vision, inspiration, and integrity, influences the creation of a great organization? Purpose: We explored what actual leading with vision, inspiration, and integrity means. The main goal is to determine the contribution of each segment to achieving lasting excellence of the organization. Method: For the purpose of the research, we used a qualitative method. We made a study of the literature and analyzed the obtained data. Results: Research has shown that leading with vision, inspiration and integrity, as one of the concepts of the EFQM excellence model, is one of the key factors in achieving an excellence organization. To achieve maximum effects, all three segments, vision, inspiration and integrity, have to be consider in a synergistic sense. Organization: Through research, the organization gained an overview of different management approaches and their effectiveness in encouraging employees to work to the best of their ability. Society: The organizations contributes to the sustainable and comprehensive well-being of all employs by investing in the education of leaders in the field of leadership and personal growth, and by investing in the development of ethical and moral behavior. Originality: In the research, we presented one of the eight concepts of the EFQM excellence model, Leading with vision, inspiration and integrity, and analyzed the FOŠmeter Business Excellence – a scorecard which summarizing the results of self-assessment of parent organizations of the FOŠ Summer School »Business Excellence« for year 2018 and 2020. Limitations/Future Research: The research was limited to the collected and reviewed literature and the results of the self-assessment of a small number of participants in the FOŠ Summer School. It would make sense to continue the research or extend it to include a quantitative method that would result in the statistical characteristics obtained and could thus be extended to the whole population.